Health related quality of life in patients with diabetic foot ulceration — translation and Polish adaptation of Diabetic Foot Ulcer Scale short form. Issue 1 (January 2017) - Macioch, Tomasz; Sobol, Elżbieta; Krakowiecki, Arkadiusz; Mrozikiewicz-Rakowska, Beata; Kasprowicz, Monika; Hermanowski, Tomasz
Abstract Objectives Diabetic foot ulcer (DFU) is a common complication of diabetes and not only an important factor of mortality among patients with diabetes but also decreases the quality of life. The short form of Diabetic Foot Ulcer Scale (DFS-SF) provides comprehensive measurement of the impact of diabetic foot ulcers on patients' health related quality of life (HRQoL). The purpose of this study was to translate DFS-SF into Polish and evaluate its psychometric performance in patients with diabetic foot ulcers. Methods The DFS-SF translation process was performed in line with Principles of Good Practice for the Translation and Cultural Adaptation Process for patient reported outcome measures (PROMs) developed by ISPOR TCA group. Assessment of the reliability and validity of Polish DFS-SF was performed in native Polish patients with current DFU. Results The DFS-SF validation study involved 212 patients diagnosed with DFU, with 4.4 years of DFU duration on average. The average ulcer size was 5.5 sq. cm, and generally only one limb was affected. Men (72%) and type 2 diabetes patients (86%) prevailed, with 17.8 years representing the mean time since diagnosis. The mean population age was 62.5 years. The internal consistency of all scales of the Polish DFS-SF was high (Cronbach's alpha ranged from 0.82 to 0.93). Item convergent and discriminant validity was satisfactory (median corrected item-scale correlation ranged from 0.61 to 0.81). The Polish DFS-SF demonstrated good construct validity when correlated with the SF-36v2 and showed better psychometric performance than SF-36v2. Conclusions The newly translated Polish DFS-SF may be used to assess the impact of DFU on HRQoL in Polish patients.